Toothpaste with nanosized trimetaphosphate reduces enamel demineralization - Souza, M. D.B. [UNESP]; Pessan, J. P. [UNESP]; Lodi, C. S. [UNESP]; Souza, J. A.S. [UNESP]; Camargo, E. R.; Souza Neto, F. N.; Delbem, A. C.B. [UNESP] (SAGE Publications, 2017)
This double-blind crossover study assessed the effects of a low-fluoride (low-F) dentifrice containing nanosized sodium trimetaphosphate (TMP) on enamel demineralization in situ. Nineteen subjects wore palatal appliances containing 4 blocks of bovine enamel and were randomly assigned to brush their teeth with placebo (without F/TMP), 250-ppm F (250F), 250F plus 0.05% nanosized TMP (250F-TMPnano), and 1,100-ppm F (1,100F) dentifrices during 7 d, under cariogenic challenge. Enamel surface hardness and cross-sectional hardness (ΔKHN [Knoop hardness number]), as well as F, calcium (Ca), and phosphorus (P) concentrations, were determined. Also, biofilm that formed on the blocks was analyzed for F, Ca, P, and insoluble extracellular polysaccharide concentrations. Data were submitted to analysis-of-variance models and Student-Newman-Keuls test (P < 0.05). The 250F-TMPnano dentifrice promoted the lowest ΔKHN among all groups (P < 0.001), while the percentage of surface hardness loss was similar to 1,100F. Also, similar F, Ca, and P concentrations in enamel were observed for 1,100F and 250F-TMPnano. In the biofilm, the highest F content was observed for 1,100F; Ca content was similar between 1,100F and 250F-TMPnano; and P content was similar among all groups. Similar extracellular polysaccharide values were observed for 250F-TMPnano and 1,100F (P < 0.001), ionic activity of CaHPO0 4, CaF+, and HF0 (P < 0.05) and degree of saturation of hydroxyapatite and CaF2 (P < 0.05). It was concluded that the protective effect of 250F-TMPnano dentifrice was similar to a conventional dentifrice for most of the variables studied, having a more pronounced effect on the subsurface lesion when compared with the conventional toothpaste (1,100F). Knowledge Transfer Statement: Although toothpastes containing ≥1,000-ppm fluoride are more effective than low-fluoride formulations against dental caries, their early use can lead to side effects. This has prompted intensive research on alternatives to increase the anticaries effect of lowfluoride toothpastes. The present in situ study demonstrated that the addition of sodium trimetaphosphate nanoparticles to toothpastes containing 250-ppm fluoride significantly enhances the protective effect of this formulation against enamel demineralization to levels comparable to a 1,100-ppm fluoride toothpaste in terms of most of the variables studied. Most important, this formulation promoted the lowest loss of subsurface hardness among all groups, suggesting that caries lesions would take longer to develop under clinical conditions when compared with a conventional (1,100-fluoride) toothpaste.
Keywords: Dental plaque; Dentifrices; Fluorides; Hardness; Nanotechnology; Phosphates